Językowy obraz przestrzeni wiejskiej jako właściwość postfolkloru w powieści Wiesława Myśliwskiego "Kamień na kamieniu" = The linguistic image of rural space as a feature of post-folklore in Wieslaw Myśliwski`s novel "Stone upon Stone" - Malczyk, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The sketch is an attempt to discuss the linguistic image of the village space in "Stone upon stone" by Wiesław Myśliwski. The article presents a short biography of Wiesław Myśliwski and a definition of the linguistic image of the world. Human attachment to the sourrounding nature is revealed by usage of certain measures. These are as follows: quoting examples of names of locations and descriptions of the rural space, stimultaneously ta king into account the divisions of place sinto tame and dangerous ones as well as those sacred and those chich are not.
Keywords: Myśliwski, Wiesław (1932- ); postfolklor; przestrzeń; językowy obraz świata; post-folklore; space; linguistic image of the world